1992
DOI: 10.1136/bjo.76.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and management of the 'detached' rectus muscle.

Abstract: The clinical features and management of 17 cases of detached extraocular muscles are described. They are classified into four groups: (1) the muscle which is cut and lost during squint surgery, (2) the muscle which breaks during squint surgery, (3) the muscle which slips following squint surgery, and (4) the muscle which is damaged during facial or orbital trauma. The prognosis for group 1 is poor whereas groups 2-4 have a good chance of successful muscle relocation. Figure 2 The muscle which snaps leaves a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 4 publications
(3 reference statements)
1
28
0
Order By: Relevance
“…Aggressive orbital dissection should be avoided because this may result in laceration of Tenon's capsule with manipulation of orbital fat and, consequently, the development of a fat adherence syndrome [1,3]. The most indicated repair technique in a case treated soon after the injury is reattachment of the torn ends of the muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aggressive orbital dissection should be avoided because this may result in laceration of Tenon's capsule with manipulation of orbital fat and, consequently, the development of a fat adherence syndrome [1,3]. The most indicated repair technique in a case treated soon after the injury is reattachment of the torn ends of the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, these procedures carry an increased risk of anterior segment ischemia, especially in older patients [1,3]. IOAT, first described by Elliot and Nankin in 1981 [8], might be an alternative treatment in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Medial rectus (MR) muscles lost during strabismus surgery are rarely found. 4 A lost MR muscle is usually expected in the presence of an overcorrection after esotropia (ET) surgery or undercorrection after exotropia (XT) surgery, resulting in limited duction in the field of action of the muscle. We present 3 cases of successful conventional strabismus surgery to retrieve lost MR muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Plager & Parks (1990) reported that 67% of lost superior, inferior, and lateral rectus muscles were retrievable while only 10% of lost medial rectus muscles were retrievable. MacEwen et al (1992) found that medial rectus muscles that were cut and lost during strabismus surgery are seldom located, but snapped or traumatically severed muscles are frequently located.…”
Section: Introductionmentioning
confidence: 99%